Обессоливание сточных вод предприятий черной металлургии - Резников Ю. Н. Юрий Николаевич; Граховский Б. М. Борис Максимович; Мягкий Д. Д. Джон Дмитриевич; Каленский И. В. Игорь Владимирович (Киев, Технiка, 1984)
Авт. указаны на обороте тит. л.